2023
DOI: 10.21203/rs.3.rs-2487922/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alleviating iatrogenic effects of paclitaxel via anti-inflammatory treatment

Abstract: Background Paclitaxel is touted as an essential medicine due to its extensive use as a chemotherapeutic for various cancers and an antiproliferative agent for restenosis. Due to recent concerns related to long-term mortality, paclitaxel (PTX)-based endovascular therapy is now surrounded by controversies. Objective Examine the inflammatory mediators driven by the systemic administration of PTX and explore the means to suppress these effects. Methods RNAseq analysis, cell and mouse models. Results RNAseq analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…(2023) [382] examined the effects of PAC treatment in HUVECs and found that PAC increased the expression of pro-inflammatory factors, like TNF, IL-2 and IL-6, as well as the monocyte chemoattractant protein-1 (MCP-1) and CD137, which has been shown to induce CAMs in ECs [383,384]. Additionally, they could show that treatment of mice with PAC significantly increased the expression of the CAMs E-selectin and VCAM-1 in mouse aortic ECs in vivo [382].…”
Section: The Microtubule-stabilizer Pac Bears No Anti-inflammatory Po...mentioning
confidence: 99%
“…(2023) [382] examined the effects of PAC treatment in HUVECs and found that PAC increased the expression of pro-inflammatory factors, like TNF, IL-2 and IL-6, as well as the monocyte chemoattractant protein-1 (MCP-1) and CD137, which has been shown to induce CAMs in ECs [383,384]. Additionally, they could show that treatment of mice with PAC significantly increased the expression of the CAMs E-selectin and VCAM-1 in mouse aortic ECs in vivo [382].…”
Section: The Microtubule-stabilizer Pac Bears No Anti-inflammatory Po...mentioning
confidence: 99%